2014
DOI: 10.1021/jp5024789
|View full text |Cite
|
Sign up to set email alerts
|

Electron Extraction Dynamics in CdSe and CdSe/CdS/ZnS Quantum Dots Adsorbed with Methyl Viologen

Abstract: Semiconductor quantum dots (QDs) composed of multiple components are playing an important role in solar energy conversion as light harvesting materials. Electron extraction dynamics in CdSe and core/shell CdSe/CdS/ZnS colloidal QDs are studied by femtosecond transient absorption spectroscopy in this Article. Our study demonstrates that, in the presence of the commonly used electron acceptor, methyl viologen (MV2+), electrons in the 1S state of CdSe QDs can be effectively extracted with a time constant less tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 49 publications
4
41
2
Order By: Relevance
“…The obtained rise-time was shortened by the complex formation: the risetimes of ZAITe NCs and ZAITe NC-MV 2+ complexes, s rise (-ZAITe) and s rise (ZAITe-MV 2+ ), were 450 fs and 220 fs, respectively. Similar rise-time shortening was reported for CdSe NC-MV 2+ complexes 9,36 and CdSe-Au hetero NPs 17 as direct evidence for the transfer of hot electrons from NCs to acceptors, MV 2+ or Au NPs, respectively. Furthermore, it was reported that hot electrons in CdSe NCs were relaxed to the band-edge state with a lifetime of a few hundred femtoseconds to several picoseconds, being comparable to the time range of TA signal evolution shown in Fig.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…The obtained rise-time was shortened by the complex formation: the risetimes of ZAITe NCs and ZAITe NC-MV 2+ complexes, s rise (-ZAITe) and s rise (ZAITe-MV 2+ ), were 450 fs and 220 fs, respectively. Similar rise-time shortening was reported for CdSe NC-MV 2+ complexes 9,36 and CdSe-Au hetero NPs 17 as direct evidence for the transfer of hot electrons from NCs to acceptors, MV 2+ or Au NPs, respectively. Furthermore, it was reported that hot electrons in CdSe NCs were relaxed to the band-edge state with a lifetime of a few hundred femtoseconds to several picoseconds, being comparable to the time range of TA signal evolution shown in Fig.…”
Section: Resultssupporting
confidence: 79%
“…Charge separation dynamics with the use of various electron acceptors has been reported in many papers. [5][6][7][8][9][10][11][12][13][14][15][16][17] For example Banin et al reported that hybrid nanostructures of Au-tipped CdS nanorods with a larger Au size exhibited a higher probability for charge separation of multiple excitons formed in the CdS nanocrystals, improving the photocatalytic activity for H 2 generation. 15 The rate of photoinduced electron transfer from CdSe NCs to methyl viologen (MV 2+ ) was shown to be dependent on the particle morphology: plate-like CdSe NCs exhibited a slower rate than that of spherical or rod-shaped CdSe NCs due to the weak electronic coupling along the short and long axes in the lateral dimension.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the proportion of surface defects will also increase with decrease in the thickness, to some extent, modifying the carrier dynamics. These kinds of carriers slowing down phenomenon have been investigated in conventional QDs and two-dimensional films [57,59,60]. The slowed carrier cooling facilitates the carrier multiplication [23] and hot-electron transfer [12], thus enabling the higher efficiency of energy use in photovoltaic devices.…”
Section: Carrier Lifetime Modulationmentioning
confidence: 99%
“…Reducing the material dimensionality to achieve quantum confinement from one (two-dimensional material) to all three (quantum dot) dimensions is believed to slow hot-carrier cooling, since the enlarged energy spacing arising from quantum confinement causes a ‘phonon bottleneck'6. Nevertheless, the initial hot-carrier extraction efficiency in typical quasi-zero-dimensional semiconductor quantum dot systems at room temperature is still low.…”
mentioning
confidence: 99%